Hole-Carrier-Dominant Transport in 2D Single-Crystal Copper - Ok, Jong Mok; Kang, Kyungrok; Hyun, Jounghoon; Lim, Chan-Young; Gim, Seonggeon; Hwang, Jinwoong; Denlinger, Jonathan D.; Cheon, Miyeon; Regmi, Binod; Lee, Ji-Eun; Ryu, Hyejin; Kim, Su Jae; et al. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2024)
In 2D noble metals like copper, the carrier scattering at grain boundaries has obscured the intrinsic nature of electronic transport. However, it is demonstrated that the intrinsic nature of transport by hole carriers in 2D copper can be revealed by growing thin films without grain boundaries. As even a slight deviation from the twin boundary is perceived as grain boundaries by electrons, it is only through the thorough elimination of grain boundaries that the hidden hole-like attribute of 2D single-crystal copper can be unmasked. Two types of Fermi surfaces, a large hexagonal Fermi surface centered at the zone center and the triangular Fermi surface around the zone corner, tightly matching to the calculated Fermi surface topology, confirmed by angle-resolved photoemission spectroscopy (ARPES) measurements and vivid nonlinear Hall effects of the 2D single-crystal copper account for the presence of hole carriers experimentally. This breakthrough suggests the potential to manipulate the majority carrier polarity in metals by means of grain boundary engineering in a 2D geometry. The intrinsic nature of transport is presented by hole carriers in 2D copper without grain boundaries. Twin boundaries almost do not scatter electrons. The hidden hole-like properties of 2D copper can only be unmasked by thorough removal of grain boundaries. The existence of hole carriers is revealed in 2D copper through angle-resolved photoemission spectroscopy and nonlinear Hall effect measurements. image